Нормативно-правові засади функціонування органів влади та місцевого самоврядування у Луцьку в 1919–1939 рр. - Малеончук, Галина Олександрівна; Maleonchuk, Halyna O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано етапи становлення та нормативно-правові основи функціонування польських органів влади і самоврядування у Луцьку міжвоєнного періоду. Висвітлено організаційні засади створення та діяльності міської ради та магістрату, розглянуто сферу їх повноважень, рівень підпорядкування органам державної влади.

The article analyzes the stages of development and regulatory legal bases of functioning of Polish authorities and self-government in Lutsk in the interwar period. The author characterizes the legal fundamentals of their functioning, based on the decree of the Head of State about self-government in 1919, the decision of the Council of Ministers about a partial change of system of self-government in 1933 and orders of the Commissioner the eastern lands and city rules and regulations. The article outlines the organizational principles of the creation, composition and structure, and the scope of activities of city council and magistrate, which were self-government in Lutsk during 1919 – 1939. City Council performed regulatory functions, magistrate – executive. The Supervisory authority, which regulates the city council and magistrate were in different periods commissioners, district elder and voivode. The Author traces the transformation of the city self-government from the influential institutions to complementary to Polish government circles.
Legal principles of functioning the authorities and self-government in Lutsk in 1919 – 1939
Keywords: Друга Річ Посполита; Second Polish Commonwealth; влада; government; самоврядування; self-government; Луцьк; Lutsk; міська рада; city council; магістрат; magistrate